UPAYA BRANDING TEMPAT WISATA ALAM PANGJUGJUGAN MELALUI VIDEO PROMOSI DI MEDIA SOSIAL - Asep Abidin; Sri Suharti; Nani Ernawati; Ahmad Muhammad Ryad Saiful Hakim (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
The Pangjugjugan natural tourist spot branding activity aims to increase visibility and tourist attraction through digital promotion. The method used is participatory observation, where the community service team identifies tourism potential through direct observation, then creates video content that highlights the uniqueness of the tourist spot. The video is shared through team members' social media to expand the reach of the promotion. The results of the activity show an increase in tourist interaction and interest in Pangjugjugan, as well as positive changes in managers who are more active in utilizing social media. This branding is expected to have a long-term impact in the form of increased visits and strengthening of tourism identity. Keywords: branding, social media, Pangjugjugan, tourism